Numerical study on drag and lift coefficients of a marine riser at high Reynolds number using COMSOL multiphysics - Ahmad, M. Faizal (2020)
Flow around a marine riser in water at the drag crisis regime was investigated using numerical modelling. In this regime, the drag coefficient drops off at a certain Reynolds number due to a change from laminar to turbulent flow. The aim is to investigate the capability of turbulence model to predict drag coefficient through COMSOL Multiphysics, a computational fluid dynamic (CFD) transient solver and compared against existing numerical models and experiment by Maritime Research Institute Netherlands (MARIN). Numerically, drag and lift forces depend on the point of separation from the cylinder in which different turbulence modelling will result in varying separation point and will lead to different vortex formation and the drag force. Reynolds Average Navier-Stokes (RANS) was employed using the k-ϵ and Menter's Shear Stress Transport (SST) turbulence model in two-dimensional CFD simulation. Six Reynolds numbers, similar to the test case, were considered. It can be concluded that the standard k-ϵ turbulence model, can only provide a good approximation at high turbulence regime, which is Reynolds number of 3.15 ° 105 and higher. While, SST turbulence model can provide a good approximation at subcritical regime which before the sudden drop of drag force regimes.